Noun Form of Address of Characters in the 21 Jump Street Movie - Dewi, Luh Ledi Ruscita; Indrawati, Ni Luh Ketut Mas (Humanis, 2021)
This study is aimed to identify the types of noun form of address and describing the function of noun form of address applied in the movie. The data of this study was taken from a movie entitled 21 Jump Street as the primary data. The data was collected by documentation method and note taking technique. A qualitative method was used to analyze the data. It means the data was described based on theories applied in this study. The theory proposed by Braun was used to analyze the types of noun form of address. Whereas, the theory proposed by Brown and Gilman was used to analyze the function of noun form of address applied by characters in the movie. The results found five types of noun form of address, namely; names term (first name, last name and nickname), kinship term, title, occupational term, terms of endearment. This study does not find any data related to the abstract noun because this movie does not have any scenes which describe the abstract quality of the addressee, such as in the kingdom or court. Moreover, the function of noun form of address terms to show solidarity becomes the highest occurrences in the movie.